A hybrid partial and general equilibrium modeling approach to assess the hydro-economic impacts of large dams – The case of the Grand Ethiopian Renaissance Dam in the Eastern Nile River basin. (July 2019) - Kahsay, Tewodros Negash; Arjoon, Diane; Kuik, Onno; Brouwer, Roy; Tilmant, Amaury; van der Zaag, Pieter
Abstract: A novel integrated hydro-economic modeling framework that links a bottom-up partial equilibrium (engineering) model with a top-down (economic) general equilibrium model is developed for assessing the regional economic impacts of water resources management and infrastructure development decisions in a transboundary river basin. The engineering model is employed first to solve the water allocation problem for a river system in a partial equilibrium setting. The resulting system-wide changes in optimal water allocation are subsequently fed into the general equilibrium model to provide an economy-wide perspective. This integrated hydro-economic modeling framework is illustrated using the Eastern Nile River basin as a case study. The engineering-based stochastic dual dynamic programming (SDDP) model of the Eastern Nile basin is coupled with the computable general equilibrium (CGE) model GTAP-W to assess the economy-wide impacts of the Grand Ethiopian Renaissance Dam (GERD) on the Eastern Nile economies. Highlights: A hybrid hydro-economic modeling approach is developed combining existing models. The value added of the new model is tested on the Grand Ethiopian Renaissance Dam. Optimal water allocation is simulated using a stochastic-dynamic engineering model. Results feed into a macro-economic model for a basin and economy-wide perspective. Integrated modeling increases the credibility of the economy-wide impacts of dams.